OPTIMALISASI FUNGSI PERPUSTAKAAN UNTUK MENDUKUNG TUJUAN PEMBANGUNAN BERKELANJUTAN (SDGS) DI DESA ROOMO - Suharto, Suharto; Umar Burhan (Asosiasi Dosen Muda Indonesia, 2024)
Abstract: The library is an institution that provides books including books on science and technology to its members so that these members can add to their knowledge and technology. Roomo Village, Manyar District, Gresik Regency has provided a village library so that the people of Roomo Village can add to their knowledge and technology. Science and technology will drive the achievement of the Sustainable Development Goals. Roomo Village, Manyar District, Gresik Regency is an advanced village that has a Village Library as a pilot in Gresik Regency. The current existence of the library is less than optimal due to the inadequate condition of the library as a library. This community service program aims to optimize the function of the Roomo Village library. After evaluation, to optimize the function of the library, it is necessary to: 1. Improve book administration; 2. Arrangement of books; 3. Improvement of Facilities. This community service program is very important because the results make it optimal for the library to improve science and technology for the people of Roomo Village. Keywords: Libraries, Literacy, SDGs, Villages